Racionalizace výroby tělesa brusky - Mišelnický, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Práce je zaměřena na racionalizaci výroby Tělesa brusky, jakožto speciálního příslušenství pro svislý soustruh s typovým označením BASICTURN 1250 od firmy TOSHULIN, a.s. V práci jsou popsány problémy současné výroby a navrženy konstrukčně-technologické úpravy tak, aby bylo docíleno snížení nákladů na výrobu a celkové zefektivnění výroby.

The thesis is focused on the rationalization of the grinding body production as a special accessory for a vertical lathe with the type designation BASICTURN 1250 from the company TOSHULIN PLC. The thesis describes the problems of the current production and suggests the constructional and technological adjustments in order to achieve a reduction of the production costs and the overall production efficiency.
Rationalization of grinder body production
Keywords: Racionalizace; těleso brusky; zefektivnění; inovace; Rationalisation; body grinders; effectiveness; innovation